Case of Human Infestation with Dermanyssus gallinae (Poultry Red Mite) from Swallows (Hirundinidae) - Georgios Sioutas; Styliani Minoudi; Katerina Tiligada; Caterina Chliva; Alexandros Triantafyllidis; Elias Papadopoulos (Pathogens, 2021)
Dermanyssus gallinae (the poultry red mite, PRM) is an important ectoparasite in the laying hen industry. PRM can also infest humans, causing gamasoidosis, which is manifested as skin lesions characterized by rash and itching. Recently, there has been an increase in the reported number of human infestation cases with D. gallinae, mostly associated with the proliferation of pigeons in cities where they build their nests. The human form of the disease has not been linked to swallows (Hirundinidae) before. In this report, we describe an incident of human gamasoidosis linked to a nest of swallows built on the window ledge of an apartment in the island of Kefalonia, Greece. Mites were identified as D. gallinae using morphological keys and amplifying the Cytochrome C oxidase subunit I (COI) gene by PCR. Bayesian phylogenetic analysis and median-joining network supported the identification of three PRM haplogroups and the haplotype isolated from swallows was identical to three PRM sequences isolated from hens in Portugal. The patient was treated with topical corticosteroids, while the house was sprayed with deltamethrin. After one week, the mites disappeared and clinical symptoms subsided. The current study is the first report of human gamasoidosis from PRM found in swallows’ nest.